The enforceability of jurisdiction clauses against a third-party holder of the bill of lading - Nahia Arostegi Arrillaga (Estudios de Deusto)
This essay explores the enforceability of jurisdiction clauses against a third-party holder of the bill of lading under the Spanish and European Private International Law. The analysis addresses the tension between Regulation Brussels I bis article 25(1) and the Spanish Maritime Navigation Act (MNA) articles 251 and 468, which impose additional validity requirements. The essay evaluates the European Court of Justice’s recent ruling in joined cases C-345/22 to C-347/22, clarifying how to determine the applicability of jurisdiction clauses against a third-party holder of the bill-of lading and explaining that the Spanish additional requirement of individual and separate negotiation of the clauses is not applicable when Regulation Brussels I applies. Ultimately, the paper highlights the primacy of EU law over conflicting national provisions and its implications for legal certainty in contracts of carriage of goods by sea.